2017
DOI: 10.1007/s10298-017-1114-3
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus globulus (Labill.): a perfume tree with several medicinal purposes

Abstract: Eucalyptus globulus (Labill.) [Myrtaceae] est originaire de Tasmanie en Australie et pousse surtout dans les régions chaudes. L'eucalyptus commun ou gommier bleu est un arbre sempervirent qui peut croître jusqu'à 30-55 m de haut. Ses feuilles sont la principale source de son huile essentielle (HE). Utilisée pour ses vertus médicinales, notamment antitussives et expectorantes, elle n'en a pas moins des propriétés fébrifuges, toniques, astringentes, antiseptiques, hémostatiques et vermifuges. Parmi ces composés… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
2
0
2
Order By: Relevance
“…A previous study by Boughendjioua (2017) showed that the yield of lavender EO from Skikda (East Algeria) was 1.5%, while the yield of lavender essential oil from Zagreb in central Croatia was 0.9% (Blažeković et al (2018). Variation in EO yields could be attributed to various factors, including environment, agronomy, age, genotype, and climate (Bey-Ould Si Said et al 2016;Boukhatem et al 2017), as well as harvest period, extraction method and conditions, and recovery percentages (Bagheri et al 2014), lavender flower maturity and interaction with the environment.…”
Section: Extraction Kinetics and Yield Of Essential Oil Of Lavandula ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Boughendjioua (2017) showed that the yield of lavender EO from Skikda (East Algeria) was 1.5%, while the yield of lavender essential oil from Zagreb in central Croatia was 0.9% (Blažeković et al (2018). Variation in EO yields could be attributed to various factors, including environment, agronomy, age, genotype, and climate (Bey-Ould Si Said et al 2016;Boukhatem et al 2017), as well as harvest period, extraction method and conditions, and recovery percentages (Bagheri et al 2014), lavender flower maturity and interaction with the environment.…”
Section: Extraction Kinetics and Yield Of Essential Oil Of Lavandula ...mentioning
confidence: 99%
“…It multiplies the possibilities of use from one region to another. The variability depends on pedoclimatic factors, but harvest periods, duration of sunshine, rainfall, altitude, and the nature of the soil influence the chromatographic profile of EOs (Boukhatem et al 2017). In this context, this study aims to characterize the EO of Lavandula officinale (Lavandula angustifolia) harvested in the Seraïdi region (Northeastern Algeria) and to evaluate its antifungal, antibacterial and antioxidant activities to confirm its applications as a fungicide and bactericide, to reduce the harmful effects the traditional pesticide but also its use as an antioxidant agent to replace the chemical antioxidants used in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Ses feuilles sont la principale source de son huile essentielle. Utilisée pour ses vertuesmedecinales, notamment antitussive et expectorantes, elle n'en a pas moins des proprietés fébrifuges, toniques, astringentes, antiseptiques, antimicrobiennes, hémostatiques et vermifuges (Boukhatem et al, 2019;Salehi et al, 2019).…”
Section: Introductionunclassified
“…Também tem propriedades antifúngicas, analgésicas e antiinflamatórias (Pombo et al, 2018). Ademais, destaca-se também, o óleo essencial do Eucalipto globulus no tratamento de infecções respiratórias (Boukhatem et al, 2017). Além disso, apresentam-se como agente antimicrobiano (Abirami et al, 2017, Monteiro et al, 2021.…”
Section: Introductionunclassified